Constituição do campo sensível : apegos, renúncias e liberdade : uma contribuição da filosofia budista - Souza, Carlos Henrique Amaral de (2012)
This essay has been written based on an interface with the millennial oral transmission of the Buddhist philosophy. Through the perspective of a “practical philosophy”, we constitute a methodology in which the matters unfold revealing intermingled reflections and ideas, with the intent of contemplate a topic and its several different angles, based on the Buddhist teachings of the Sakya lineage, which lead us to an ethical posture for the everyday life. We cover “guidelines for life” present on the teachings emphasizing mind control, the motivation and the intentions of the human action. In order to accomplish this ethical exercise, capable of transfor ming education itself – the teaching and learning process – and also the knowledge acquirement – the constitution of knowledge about oneself and the world -, the practice of meditation finds its way as the outliner of new aspects for the thinking, feeling and acting processes, which is highlighted through the classical teaching on “Parting from the Four Attachments”, a key reference to our work. On this perspective, we discuss meditation as a field of the experience, a method through which we may live the “non-separation of subject-body-mind”. The importance of meditation for the creation of a constitutive experience process to the awakening state of mind. Whatever we do through practices in which “we are the experience of our minds”, “we are the mind itself”, and the practice of meditation provides us with this experience. The experience of “being present in each moment” may lead us to a state in which we can control ourselves, the recognition of others as human beings which we all are and the development of compassion for all beings. Through this process, we may recognize the Buddhic state, or better yet, the Buddheity state which we all potentially have. Buddha is a power within us, a power of developing equanimous compassion for all beings and we may do that by recognizing two important aspects: the four attachments which imprison us and the way we get rid of them to walk the awakened way